Women’s presence and visibility in management roles at universities - Sanchez-Moreno, Marita; Tomás Folch, Marina; Lavié Martinez, José Manuel (Education Policy Analysis Archives, 2013)
This paper explores the debate on women’s presence and visibility in management roles at universities, as well as the nature of power when exercised by those women. We discuss the results from research carried out through a descriptive inquiry into two state-funded Spanish universities. We developed our analyses through the information we collected by using three different data collection strategies: semi-structured interviews, analysis of institutional websites, and focus groups. Our results show that both visibility and the exercise of power are issues directly related to gender. There seems to prevail a certain degree of women’s invisibility in the two universities we studied. Sociocultural characteristics that have pervaded female academics’ lives, as well as the structural circumstances that are currently present in Spanish universities, are two of the main factors that may account for this invisibility.